2017
DOI: 10.1088/1758-5090/aa6725
|View full text |Cite
|
Sign up to set email alerts
|

Surface micromorphology of cross-linked tetrafunctional polylactide scaffolds inducing vessel growth and bone formation

Abstract: In the presented study, we have developed a synthetic strategy allowing a gradual variation of a polylactide arms' length, which later influences the micromorphology of the scaffold surface, formed by a two-photon polymerization technique. It has been demonstrated that the highest number of cells is present on the scaffolds with the roughest surface made of the polylactide with longer arms (PLA760), and osteogenic differentiation of mesenchymal stem cells is most pronounced on such scaffolds. According to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…In this work we took advantage of various state-of-the-art techniques helping to understand biodegradation of biomeshes: non-invasive fluorescence imaging developed for in vivo estimation of the dynamics of the biodegradation rate of such implants (Timashev et al, 2016;Kuznetsova et al, 2017), in vivo imaging of implant (de)oxygenation using O 2 -PLIM, ex vivo using multiphoton tomography, and conventional histological techniques. Before the implantation, we analyzed proteolytic stability and cytotoxicity of DBP samples in vitro (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we took advantage of various state-of-the-art techniques helping to understand biodegradation of biomeshes: non-invasive fluorescence imaging developed for in vivo estimation of the dynamics of the biodegradation rate of such implants (Timashev et al, 2016;Kuznetsova et al, 2017), in vivo imaging of implant (de)oxygenation using O 2 -PLIM, ex vivo using multiphoton tomography, and conventional histological techniques. Before the implantation, we analyzed proteolytic stability and cytotoxicity of DBP samples in vitro (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Collagen and elastin have several fluorescent moieties in the ultraviolet and visible spectral regions (Croce and Bottiroli, 2014) that may account for the DBP fluorescence. To assess biodegradation of the biomeshes, we used a special technique developed earlier for bone implants having a fluorescence signal (Timashev et al, 2016;Kuznetsova et al, 2017). In brief, we analyzed the fluorescence of implanted pericardium tissue using an Axio Zoom V16 (Carl Zeiss, Germany) fluorescence stereomicroscope and ImageJ 1.43u software (National Institutes of Health, United States).…”
Section: Fluorescence Stereomicroscopymentioning
confidence: 99%
“…The SEM images showed that obvious swelling occurred in the GH/B and GH/A/B scaffolds after cross-linking and the diameter of fibers increased significantly, which may not conducive to cell adhesion and proliferation. Studies had shown that cell proliferation on scaffolds could be promoted by regulating the surface topography, 38 such as HA and ion-doped HA could be used to modify scaffolds' architecture and properties, including surface crystallinity, roughness, surface charge, and scaffold rigidity, to promote the osteogenic differentiation of stem cells and bone formation. 39 Significantly, the created osteogenic microenvironment within scaffolds is critical for generating best repairing effects.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are more aspects to bone regeneration than just geometry [ 109 ]. Customised 3D printed bone implants and scaffolds should also be biologically active to restore the functional characteristics of patient’s bone such as vascularization for an appropriate diffusion of oxygen, nutrients and waste products [ 110 ]. Furthermore, it is critical to consider how the patient’s neuromusculoskeletical system might adapt to satisfy the new dynamic moment requirements at each joint during everyday activities [ 111 ].…”
Section: Resultsmentioning
confidence: 99%